The Contribution of Leadership Behavior and Work Motivation Professional Competency Teachers In Islamic Senior High School Pangkalan Susu District - Yahfizham, Rosida Hanum Nst (International Journal Of Education, Social Studies, And Management (IJESSM), 2021)
This study discusses the Contribution of Leadership Behavior and Work Motivation with Professional Competence in Islamic Senior High School in Pangkalan Susu District which aims to find out 1). How is the contribution of Leadership Behavior with Teacher Professional Competence in Islamic Senior High School Pangkalan Susu District, 2). How the Contribution of Work Motivation with Professional Competence of Teachers in Islamic Senior High School in Pangkalan Susu District, 3). How is the contribution between Leadership Behavior and Work Motivation with Professional Competence of Teachers in Islamic Senior High School in Pangkalan Susu District. This type of research is quantitative with multiple regression. The population in this study amounted to 51 teachers and the study was conducted with a total sample. The technique used in analyzing the data is to use the Multiple Regression technique. The results of this study indicate that there is a relationship between Leadership Behavior and Work Motivation with Professional Competence in Islamic Senior High School in Pangkalan Susu District. This is evidenced by the calculation of the variables of Leadership Behavior and work motivation on the professional competence of teachers of 0.543 with a probability (p) of 0.000. Because the probability value (p) < 0.05, Ho is rejected and H1 is accepted. This means that leadership behavior and work motivation make a significant contribution to the professional competence of teachers in Pangkalan Susu District